SYNERGY OF AUDIT AND ACCOUNTABILITY OF SOCIAL ASSISTANCE FUND - R Umihany; Tenriwaru Tenriwaru; M Reza (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2022)
Purpose – This study was conducted to see the Synergy between Auditing and Accounting of Social Assistance Funds Based on the Religious Paradigm Design/methodology/approach – This study uses primary data obtained directly through direct interviews with BPK RI South Sulawesi Province, Makassar City Social Service, La'latang Village, RT / RW, as well as receiving and not receiving social assistance. Findings – The results of this study indicate that government employees have not implemented accountability in disbursing social assistance funds. Originality – This study uses primary data obtained directly through direct interviews with BPK RI South Sulawesi Province, Makassar City Social Service, La'latang Village, RT / RW, as well as receiving and not receiving social assistance. Keywords: Auditing, Accountability, Social Assistance Fund Paper Type Research Result